(untitled) - Food and Agriculture Organization of the United nations (Rome, 2008)
This manual deals with risk-based inspection of primary production operation and food pracessing establishments.
Keywords: Food adulteration and inspection,Kiểm tra thực phẩm giả; Handbooks, manuals, etc,Sách hướng dẫn